Weight regain and associated metabolic impacts on patients in a single center - Alsowaina, Khalid; Almutairi, Talal; Alzelfawi, Lama; Altamimi, Reem; Aldokhail, Laila; Alaradi, Lujain; Alrowais, Shahad (International Surgery Journal, 2024)
Background: Obesity is a global health concern, with 4 million people dying in 2017. Bariatric surgery, particularly sleeve gastrectomy, is effective but has been linked to weight regain. Studies show that only 20% of patients can keep weight off, and 60% require additional surgery due to weight regain. This retrospective study aims to measure long-term outcomes of gastric sleeves and associated risk factors. Methods: A retrospective study utilizing patient records from 2018 to 2023 aims to collect data from the medical records of individuals aged 15-70 years in Prince Sultan Military Medical City (PSMMC). Patients who were under 15 years old or above 70 years old and those who underwent other types of bariatric surgeries or complications not related to the procedures were excluded. Results: One hundred and forty-one sleeve gastrectomy patients were analyzed. The mean age was 36.8 (SD=12.9) years, with 51.8% being over 35 years old. Additionally, female patients were dominant (70.9%). No significant differences were observed in the mean values of low density lipoprotein (LDL), triglyceride, and cholesterol before and after the surgery (p>0.05). Conclusions: This study has found that sleeve gastrectomy is an effective surgical intervention for significantly improving metabolic parameters, including body mass index (BMI), glycated hemoglobin (HbA1c), blood pressure, creatinine, and high density lipoprotein (HDL) levels. No significant changes were observed for LDL, triglycerides, and total cholesterol. The study suggests that sleeve gastrectomy can lead to durable metabolic benefits irrespective of patient demographics, and further research is needed to evaluate its sustainability.